Chemical thermodynamics : basic theory and methods - Klotz, Irving M. (Irving Myron), 1916-2005 (John Wiley & Sons, 1994)
This classic textbook presents the logical foundations of the theory of thermodynamics, while teaching the reader to apply the theory to practical problems in chemistry, biology, and geology. The text adheres to the classical approach, rather than the statistical viewpoint, stressing the operational side of abstract problems. Includes problems and solved examples. Uses the classical (phenomenological) approach to thermodynamics as opposed to the statistical. Applies theory to chemical, biological and geological problems. Provides complete coverage of essential mathematical tools and computational techniques. This edition contains new chapters on thermodynamics of the electrochemical cell, Eh/pH diagrams, a revised chapter on estimation of thermodynamic properties plus treatment of the latest work in electrolyte solutions. Additional problems reflect new applications.